Peran Pendidikan Agama Kristen dalam Mengembangkan Moralitas Remaja di Era Teknologi dan Digitalisasi - Tambunan, Ruhut Parningotan; Arifianto, Yonatan Alex (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2024)
This research investigates the importance of Christian Religious Education in the ethical development of adolescents in a digital age characterized by many challenges and opportunities. The context of this issue relates to the rapid influence of technological advancements on adolescents' learning and interaction modalities. This research aims to examine the way Christian religious education instills moral principles such as honesty, compassion, and integrity to adolescents amidst the temptations presented by the digital landscape. The methodology used was qualitative, incorporating analysis of data collected from observations, interviews, and literature reviews. Findings show that Christian religious education has proven to be effective in conveying moral values through the incorporation of digital curriculum, thus fostering responsible and integrative individuals among adolescents. Nevertheless, significant challenges arise in adapting Christian religious education to align with the needs of adolescents in the digital age to ensure its continued relevance. In conclusion, Christian education is critical in cultivating adaptive